Development and validation of a Chinese medication literacy measure. (5th May 2017) - Yeh, Ying‐Chih; Lin, Hsiang‐Wen; Chang, Elizabeth H.; Huang, Yen‐Ming; Chen, Yu‐Chieh; Wang, Chun‐Yu; Liu, Jen‐Wei; Ko, Yu
Abstract: Background: Despite the impact of medication literacy (ML) on patients' safe use of medications, existing instruments are mostly for general health literacy measurement or designed for specific disease populations, with few specifically designed for ML. Objective: To develop and validate the first Chinese medication literacy measure (ChMLM). Methods: The ChMLM was developed by a multidisciplinary and bilingual expert panel and subsequently pilot‐tested. The final version had 17 questions in four sections: vocabulary, non‐prescription drug, prescription drug and drug advertisement. Face‐to‐face interviews were administered in a convenience sample of adults with diverse sociodemographic characteristics. Internal consistency was assessed by Cronbach's alpha. Content validity was confirmed by the expert panel, and hypothesis testing was performed to assess construct validity. Results: A total of 634 adults were interviewed. The mean (SD) total ChMLM score was 13.0 (2.8). The internal validity was acceptable (Cronbach's alpha=0.72). Nine of the ten a priori hypotheses were fulfilled. Younger age, higher income and higher education levels were significantly associated with a higher ChMLM score. Furthermore, higher scores on the ChMLM were associated with higher confidence or less difficulty in writing, reading, speaking and listening abilities in a health‐care encounter. No association was found between ChMLM total scores and frequency of doctor's visits. Conclusion: The ChMLM is a valid and reliable ML measure. It may help pharmacists and other health‐care providers to target patients and problem areas that need interventions with the ultimate goal of preventing medication errors and harm.